Entrepreneurship in Conflict Area: Etic Study on Swamp Buffalo Bredeer in South Kalimantan Province - Rochgiyanti, Rochgiyanti; Arisanty, Deasy; Hastuti, Karunia Puji (Technium Social Sciences Journal, 2023)
Conflicts that occur in oil palm plantations do not always have a negative impact, but there are also positive sides as driving factors for change. The research aims to analyze the positive impact of conflict on the rise of local entrepreneurs and the supporting factors for building businesses in swamp buffalo farming communities in South Kalimantan Province. The rise of local entrepreneurs in swamp buffalo farmers not only contributed to the turning of the wheels of the rural economy but also contributed to the study of social sciences. The research was conducted by qualitative methods. The research sites are central villages of swamp buffalo farms in South Kalimantan Province, which have been entered by oil palm plantations. Interviews were conducted with farmers, formal and non-formal leaders, wholesaler, members of the police, members of NGOs, and other community members who had similar businesses. There were 84 people. Observations were made on the new business objects of the breeders. Document studies and audio-visual recordings are carried out related to the activities of breeders. Data analysis uses an ethical perspective so that an overview of entrepreneurship carried out by swamp buffalo breeders is obtained from the researcher's point of view. The results showed that there was a positive impact on conflict for swamp buffalo farmers, namely the development of the entrepreneurial spirit. This is shown by the development of natural sources of livelihood other than raising swamp buffalo, which are developed based on natural conditions so that sustainable businesses are formed. The development of entrepreneurial spirit is determined by internal factors, namely trade culture and the habit of managing a business independently; and external in the form of market certainty to accommodate farmers ' products. The conclusion is that swamp buffalo breeders can become local entrepreneurs. The implication is that there is an economic turnover in rural areas.